2013
DOI: 10.11122/ijmeb.2013.9.19.459
|View full text |Cite
|
Sign up to set email alerts
|

Türkiye’de Petrol Fiyatları, İhracat ve Reel Döviz Kuru İlişkisi: ARDL Sınır Testi Yaklaşımı ve Dinamik Nedensellik Analizi

Abstract: ÖZET Bu çalışma, 1987Bu çalışma, -2010

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 45 publications
0
2
0
4
Order By: Relevance
“…In this process, which continues until 2022, it is observed that the stability of the old deficit values and the export-import coverage ratio within the target balances has emerged as an important goal. In Chart 1 below, it is possible to see a more analytical and detailed position of the monthly change in the existence of import and export balances, especially after 2020: (Altıntaş, 2013). It should be emphasized that the position of these deviations in the balance of foreign payments deficits in the foreign trade balances, especially after 2020, has turned into an uncontrollable position, especially for 2021, as well as when interpreted as the ratio of exports to imports.…”
Section: The Recent Course Of Exports and Imports In Turkey And Devia...mentioning
confidence: 99%
“…In this process, which continues until 2022, it is observed that the stability of the old deficit values and the export-import coverage ratio within the target balances has emerged as an important goal. In Chart 1 below, it is possible to see a more analytical and detailed position of the monthly change in the existence of import and export balances, especially after 2020: (Altıntaş, 2013). It should be emphasized that the position of these deviations in the balance of foreign payments deficits in the foreign trade balances, especially after 2020, has turned into an uncontrollable position, especially for 2021, as well as when interpreted as the ratio of exports to imports.…”
Section: The Recent Course Of Exports and Imports In Turkey And Devia...mentioning
confidence: 99%
“…Bu modele dayalı olarak gerçekleştirdikleri simülasyonda petrol fiyatlarındaki artışın kısa ve uzun dönemde Türkiye'nin dış dengesini olumsuz etkileyeceği sonucuna ulaşmışlardır. Altıntaş (2013), diğer bir grup değişkenle birlikte petrol fiyatlarındaki hareketlerin ihracat üzerindeki etkisini ARDL modeline dayalı olarak araştırdığı çalışmasında petrol fiyatının Türkiye'nin ihracatını artırıcı yönde etkide bulunduğu sonucuna ulaşmaktadır. Benzer bir bulgu yine ARDL modelini kullanan Şengönül vd.…”
Section: Ulusal Literatürunclassified
“…Ham petrol fiyatındaki dalgalanmanın sektörel ihracat ve ithalat hacmi üzerindeki simetrik ve asimetrik etkisini araştırmak amacıyla ARDL ve NARDL modellerine dayalı olarak yürütülen ekonometrik analizden elde edilen bulgular Türkiye'nin dış ticaretinin hem ihracat hem de ithalat açısından genel olarak petrol fiyatındaki artışlardan pozitif yönde etkilendiğini ortaya koymaktadır. Bu bulgu daha önce Altıntaş (2013Altıntaş ( ), Şengönül vd. (2018, Yeter (2023) tarafından elde edilen sonuçlarla benzerlik göstermektedir.…”
Section: Sonuçunclassified
“…Dünya enerji fiyatlarındaki artış ihracatı pozitif etkilemektedir. Enerji fiyatlarının negatif etkisi beklenirken pozitif çıkması maliyet-ihracat ilişkisi açısından ters bir yapı gibi gözükse de Altıntaş (2013) ün Türkiye için yaptığı çalışmada bir enerji malı olan ve enerji malları fiyat endeksi içindeki payı yüksek olan petrol fiyatlarındaki yükselişe rağmen ihracatın yükselmeye devam etmesi şu nedenlerle açıklamıştır:…”
Section: Sonuç Ve Politika öNerileriunclassified